Pembelajaran Huruf Hijaiyah Menggunakan Metode Iqro` pada Anak Usia Dini di PAUD Mentari: Learning Hijaiyah Letters Using the Iqro` Method for Early Childhood at Mentari PAUD - Sukranudin (Al-Faiza : Journal of Islamic Education Studies, 2026)
The purpose of this study is to determine the development of the ability to read the hijaiyah letters of early childhood through the Iqro` method at PAUD Mentari, and to find out the fun method of teaching Iqro` to early childhood at PAUD Mentari. This type of research is qualitative research, while the data collection techniques include: interviews, observation and documentation. The results of this study found that learning using the Iqro` method is carried out by educators combining the Iqro` method with appropriate media and learning strategies so that the learning process runs fun for students. Pronouncing it and also because there are examples, students will also be easier to write it. The supporting factors in learning the Iqro` method are the existence of module books that make it easier for students and educators and the inhibiting factors are the lack of existing facilities and infrastructure while the solution taken by teachers to overcome obstacles in student learning is by approaching students.